Uso de la tierra y diversidades alfa, beta y gamma de diplópodos en la cuenca del río Otún, Colombia - Alexander Feijoo-Martínez; Julián Bueno-Villegas; Darío Hernán Ruíz-Cobo (Universitas Scientiarum)
Land use and alpha, beta, and gamma diversity of Diplopoda in the Otún basin, Colombia. Objective: To determine the relationshipbetween changes in ecosystems and agrosystems provoked by human intervention and the alpha, beta and gamma diversity of theDiplopoda in the middle basin of the Otún river. Materials and methods: In this research we used a stratified systematic design with sevensampling windows and 16 sampling points. Millipedes were divided into families and morphotypes to calculate the alpha, beta and gammadiversity related to the heterogeneity of land uses. Results: We identified 35 morphotypes from 12 families and five orders. Alpha diversityof Diplopoda revealed significant differences between land uses (P <0.05) and a decrease of richness from preserved areas to transformedareas by human activity. A high number of exclusive morphotypes were found in forest relicts and fallow with low species turnoverbetween them, while the pastures, crop fields and plantations presented similar numbers of morphotypes but the species turnover betweenthem was high (complementarity > 85%) in spite of the low diversity in the land uses, which determined the high contribution of the betadiversity to the gamma diversity of the landscape. Conclusion: The heterogeneity of land uses showed that the changes modify the structureof diversity in Diplopoda with gradients diverging from the preserved ones to the highly transformed ones.